UNIVERBIZATION AS A MEANS OF FORMING LEXICAL INNOVATIONS (BASED ON A. NELYUBA’S DICTIONARIES «LEXICAL-WORD-BUILDING INNOVATIONS») - Dumchak , I. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article univerbization is examineo as a phenomenon of the secondary nomination. The object of the research is univerbs fixed in the dictionaries «Lexical-word-building Innovations» (ed. A. Nelyuba). Basic methods of univerbization and the structure of derived univerbs are analyzed, productive suffixes are distinguished. The most useful lexical-semantic groups of univerbs of innovative vocabulary are determined and functions of univerbs are highlighted as well.